Axillary Metastasis from an Occult Tubal Serous Carcinoma in a Patient with Ipsilateral Breast Carcinoma: A Potential Diagnostic Pitfall. (8th July 2014) - Atallah, Chantal; Altinel, Gulbeyaz; Fu, Lili; Arseneau, Jocelyne; Omeroglu, Atilla
Abstract : Axillary nodal metastasis from a nonmammary neoplasia is much rarer than diseases associated with a primary breast carcinoma. However, this has to be considered in the differential diagnosis of nodal disease in patients with a history of breast cancer. Here, we report the case of a 73-year-old female with a past medical history of breast cancer, presenting with an ipsilateral axillary metastatic carcinoma. The immunohistochemical profile of the metastatic lesion was consistent with a high grade serous carcinoma. After undergoing a total abdominal hysterectomy and salpingo-oophorectomy, thorough pathological examination revealed two microscopic foci of serous carcinoma in the right fallopian tube, not detectable by preoperative magnetic resonance imaging. In this context, the poorly differentiated appearance of the metastatic tumor and positive staining for estrogen receptor, might lead to a misdiagnosis of metastatic breast carcinoma. As the therapeutic implications differ, it is important for the pathologist to critically assess axillary lymph node metastases, even in patients with a past history of ipsilateral breast carcinoma and no other known primary tumors.